Basalt scale-reinforced aluminium foam under static and dynamic loads - Li, Jun; Wu, C.; Hao, Hong; Liu, Z.; Yang, Y. (Elsevier Ltd, 2018)
© 2018 Elsevier Ltd In this paper, mechanical performance and deformation behaviour of basalt scale-reinforced closed-cell aluminium foams are investigated. Quasi-static uniaxial compressive tests on the constitutive alloy material reveal that after basalt scale reinforcement, the alloy elasticity modulus and yield strength show noticeable enhancement. Quasi-static compression tests on the foam material show that while basalt scale-reinforced aluminium foam has higher plastic crush stress and plateau stress, the densification strain is lower than non-reinforced foam. A method based on energy absorption efficiency is adopted to accurately measure the densification strain for both foam materials. In the subsequent split-Hopkinson pressure bar tests, dynamic compressive behaviour of basalt scale-reinforced aluminium foams with relative densities ranged from 14% to 33% is studied experimentally under strain rate ranging from 480/s to 1720/s. Clear material rate sensitivity is noted from the dynamic tests. The results indicate that the plateau stress of aluminium foam increases with relative density and strain rate. In addition, with the increase in strain rates, an increase in the energy absorption capacity is observed and this characteristic is beneficial when the foam material is used to absorb impact energy. A mesoscopic model based on the X-ray CT for the aluminium foam material is developed. The simulations and the test data agreed well for the quasi-static loading case. However, it is noted that the mesoscale model without consideration of the base material rate sensitivity and the entrapped gas underestimated the strength enhancement under dynamic loading scenario.